Remittances, Transaction Costs, and Informality - Freund, Caroline; Spatafora, Nikola (2012)
Recorded workers' remittances to developing countries reached $167 billion in 2005, bringing increasing attention to these flows as a potential tool for development. In this paper, we explore the determinants of remittances and their associated transaction costs. We find that recorded remittances depend positively on the stock of migrants and negatively on transfer costs and exchange rate restrictions. In turn, transfer costs are lower when financial systems are more developed and exchange rates less volatile. The negative impact of transactions costs on remittances suggests that migrants either refrain from sending money home or else remit through informal channels when costs are high. We provide evidence from household surveys supportive of a sizeable informal sector.